The psychologisation of Eastern spiritual traditions: colonisation, translation and commodification - Cohen, Elliot (Concepts for critical psychology, 2022)
'East is East and West is West?' -- Counterculture and the Return to the East -- The Buddha as Psychologist, the Dharma as Psychotherapy -- The Dao of Psychologisation -- The Commodification of 'the East' -- Resistance -- Transpersonal Psychology.